Identification, distribution of flora and its relation to edaphic factors at U forest reserve-tools for the development of Biology teaching module - Othman Saberi, Ibrahim Husni, (Penerbit Universiti Pendidikan Sultan Idris, Tanjong Malim, 2006)
Identification, distribution of flora and its relation to edaphic factors at U forest reserve-tools for the development of Biology teaching module by Othman Saberi, Ibrahim Husni,